2021
DOI: 10.1101/2021.03.18.21253845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Longitudinal Study of BNT162b2 Vaccine-Induced Humoral Response and Reactogenicity in Health Care Workers with Prior COVID-19 Disease

Abstract: BackgroundThe SARS–CoV–2 mRNA vaccines now available are highly effective at preventing infection and afford the prospect of an end to the pandemic. Vaccines are in scare supply, however. Current recommendations in the United States are that subjects with a previous history of SARS CoV-2 infection/COVID-19 disease should receive the full vaccine regimen. This is despite the fact that prior SARS-CoV-2 infection infection confers some degree of protection and that the immune response to the vaccine is not well s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In three separate studies, baseline antibody titers of seropositive individuals were multiple folds higher than of seronegative subjects after the second vaccine dose [ 12 , 17 , 24 ]. On the other hand, some publications stated that there was no significant difference between these two groups after the second dose [ 16 , 19 , 21 ]. As a result, different recommendations can be gathered from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…In three separate studies, baseline antibody titers of seropositive individuals were multiple folds higher than of seronegative subjects after the second vaccine dose [ 12 , 17 , 24 ]. On the other hand, some publications stated that there was no significant difference between these two groups after the second dose [ 16 , 19 , 21 ]. As a result, different recommendations can be gathered from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…In two separate studies, antibody titers of seropositive individuals are multiple folds higher than those baseline seronegative subjects after the second vaccine dose [17,26]. On the other hand, some publications stated that there is no significant difference between the two groups after the second dose [27,28,29]. As a result, different recommendations can be gathered from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Kelsen et al . recommended that subjects with prior COVID-19 may require only a single dose of vaccine [29], and eventually a second dose only when the antibody levels decline significantly ( i . e ., typically, after 12 months), or in case new VBM and VoC, characterized by the so-called “escape mutations”, become endemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that seropositive groups continue to have increased Ab levels compared to seronegative groups, while others reported that there is no significant difference between the two groups. [37][38][39][40][41][42] These disparities in trend are conveyed in the rate of decline of Ab titers at 5-6 months after full immunization compared to peak levels. Among the four journal articles included in this study, two reported that seropositive groups had a larger percent decline in Ab titers from peak compared with seronegative groups.…”
Section: Serostatusmentioning
confidence: 99%